PEREDARAN IKAN KALENG YANG MENGANDUNG CACING DI KECAMATAN MARPOYAN DAMAI WILAYAH KOTA PEKANBARU TAHUN 2018 - Eko Prasetyo; Hayatul Ismi; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Canned fish are fish and fish products that have been processed, packagedin airtight cans, and given heat to kill the bacteria inside and ripen it. But sometime ago the discovery of worms in canned fish, and the type of fish is mackerel.BPOM has conducted sampling and testing of 541 fish samples in cannedcontainers consisting of 66 brands. The test results showed that 27 brandspositively contained worm parasites, consisting of 16 brands of imported productsand 11 brands of domestic products. Based on Law Number 8 of 1999, businessactors are responsible for guaranteeing the quality of goods traded. In the eventof a consumer loss, the business actor is obliged to provide compensation andanti-loss to the consumer. The purpose of this study, first is to find out theresponsibility of business actors for the circulation of canned fish containingworms and to the loss of consumers in the city of Pekanbaru, and secondly to findout the sanctions given to business actors.In this study the author uses the empirical method, another term used issociological. The study of the effectiveness of the laws that apply in society andidentify unwritten laws that apply in the community. In this case the researcherconducts research on business actors and community members in Pekanbaru,especially the Marpoyan Damai District. In collecting data, the types of data usedin this study are primary data and secondary data, namely directly throughrespondents (field), Law Number 8 of 1999 concerning Consumer Protection, LawNumber 18 of 2012 concerning Food legal journals and books - books related toresearch. Analysis of this data is done qualitatively and deductively drawnconclusions.From the results of the research in this thesis, there are two main thingsthat are concluded, namely First, the form of the responsibility of the businessactor to the loss of consumers in the City of Pekanbaru. And second, sanctionsgiven to businesses in Pekanbaru City, Marpoyan Damai District.Keywords: Consumer - Responsibility - Business actor - Consumer Protection